Energy analysis of Francis turbine for various mass flow rate conditions based on entropy production theory. (January 2022) - Yu, An; Tang, Yibo; Tang, Qinghong; Cai, Jianguo; Zhao, Lei; Ge, Xinfeng
Abstract: A methodology of the entropy production theory is employed in hydro turbine flows to analyze the hydraulic loss characteristics quantitatively. The entropy production theory has its distinctive superiority over than traditional pressure drop method because it calculates energy loss through integrating entire computational domain so that it can identify location of energy loss and reflect energy loss characteristics intuitively. This simulated study was implemented by commercial software ANSYS CFX with shear stress turbulence model for a Francis turbine versus various discharge conditions. After comparing with experimental data, the energy loss in different flow components was analyzed and the ability of flow parts to generate energy loss was evaluated versus various conditions quantitatively. Then, the distributions of entropy production rate (EPR) were displayed in stay&guide vanes, runner and draft tube. The conclusions indicate that draft tube is the main part generating the most energy loss compared with other parts. The energy loss fluctuation of runner was obtained and three dominant frequencies were captured with two low frequencies 11.93 [Hz], 15.9 [Hz] and one high frequency 27.83 [Hz]. This study indicates that entropy production theory can provide sufficient theoretical and engineering guidance for the energy loss analysis in hydro turbine flows. Highlights: A new efficiency calculation method is proposed based on entropy production theory. Entropy production theory can reflect energy loss details intuitively. The spatial distribution of energy loss in Francis turbine components was showed. The hydraulic loss regularity versus mass flow rate was revealed. The frequency between hydraulic loss and rotation keep the same.